1993
DOI: 10.1111/j.1460-2695.1993.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Growth Under Biaxial Loading

Abstract: Fatigue crack growth under biaxial loading for long cracks subjected to low cyclic stress levels was investigated. The biaxial stress ratio I ranging from -0.5 to + 1.0 was considered. The strain energy density factor range was used as the criterion for predicting the crack growth rates and crack path. The agreement between prediction and experimental results was reasonable for crack growth rates and marginal for crack paths. The investigation highlighted the inherent difficulties for crack path prediction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The problems of cracks in bi-axial fields are of the most important problems in the fracture mechanics science. Although this problem has been treated by many researchers [1][2][3][4][5][6][7][8][9][10][11][12], the problem is treated with new concepts [13][14][15][16][17][18][19][20][21][22][23][24]. The cases under study are the cracks in the fields of tension-tension, tension-compression and compression-compression with different bi-axial ratio (λ) and with different values of coefficient of…”
Section: Discussion Of Ductile Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…The problems of cracks in bi-axial fields are of the most important problems in the fracture mechanics science. Although this problem has been treated by many researchers [1][2][3][4][5][6][7][8][9][10][11][12], the problem is treated with new concepts [13][14][15][16][17][18][19][20][21][22][23][24]. The cases under study are the cracks in the fields of tension-tension, tension-compression and compression-compression with different bi-axial ratio (λ) and with different values of coefficient of…”
Section: Discussion Of Ductile Fracturementioning
confidence: 99%
“…Since former fracture theories [1][2][3][4][5][6][7][8][9][10][11][12] could not solve many of the crack problems especially for complicated fracture and cracks under complicated case of loading, a fracture theory called NN-theory was developed. The former fracture theories calculated for the energy components (S v , S d ) without considering the plastic zone due to stress concentration at crack tip in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the early findings of FCG behavior under biaxial loading, different inconsistent observations were reported. According to some researchers, in linear elastic fracture mechanics, the stress component parallel to the crack orientation has no effects on fatigue crack growth, whereas some others reported that stress biaxiality ratio affects the FCG rate under biaxial load 3–8 . Hopper and Miller reported that compressive stress on a plane parallel to the crack propagation direction can increase and tensile stress on the same plane can decrease the crack propagation rate 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of stress amplitude and stress biaxiality ratio on the FCG rates were studied and concluded that the crack growth rates are higher under negative biaxiality ratios as compared to the positive biaxiality ratio cases. Lam 8 investigated the FCG of long cracks under biaxial loads and reported that the cracks grow perpendicular to the direction of that stress which is higher among the two applied stresses for the case when λ << 1. However, when λ ≈ 1 (nearly equal to one) then the trajectory of the growing crack depends upon the initial crack orientation and is very hard to estimate.…”
Section: Introductionmentioning
confidence: 99%